(untitled) (Al-Qamar, 2021)
The Holy Qur’an is not only guidance for the world but also an excellent model of rhetoric and eloquence. Rhetoric is the art of using language for persuasion in speaking or writing, especially in oratory. From the revelation of the Qur’an up till now, the exegetical writers of the Qur’an have given this miraculous aspect of the Quran careful attention. There are two famous and modern exegeses as Muhammad ‘Alī Al-Sābūnī’s “Safwah Al-Tafāsīr” and Muhammad Ibn ‘Āshūr’s “al-Tahrīr Wa al-Tanwīr” in which, they shed light on the rhetorical aspects of the verses. Therefore, I will discuss Surah Yasin’s explanations in Urdu so that every teacher and learner of the Qur’an can get to their true meaning.